The Done‐State Derived Stative: A Case Study in Building Complex Eventualities in Syntax. (13th August 2021) - Biggs, Alison
Abstract: A basic question for theories of the syntax–semantics interface is whether the relationship between the form and meaning of complex aspectual expressions is mediated by the pieces that make up hierarchical syntax or whether complex forms and their meanings can pair directly, in templatic or constructional representations, for example. This paper examines the string I'm done writing chapter 3 with this issue in mind. The (be) done V‐ing structure does not seem to have been analyzed before, and I refer to it as the done state. The done state expresses a complex stative eventuality. Notably, the transitive object of the done state can hold a target state, an unexpected interpretation given the ‐ing verb (contrast I've been writing chapter 3 ). Apparent form–meaning mismatches of this type are regularly taken as evidence for listed, constructional mappings. I show, however, that the done state has the syntactic pieces of a stative passive of a present participle, and I argue that the done state is a previously unnoticed type of derived stative. The analysis provides a compositional account of the structure's semantics and morphology. I further argue that the syntactic items that make up the done state have the same properties that they have elsewhere in the grammar; there is no need to postulate new grammatical objects. The predictable properties of the done state find explanation in models in which complex eventualities are built up out of the minimal units that make up complex phrases.